2017
DOI: 10.1088/1748-9326/aa7c95
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer geospatial analysis of water availability for shale resources development in Mexico

Abstract: Mexico's government enacted an energy reform in 2013 that aims to foster competitiveness and private investment throughout the energy sector value chain. As part of this reform, it is expected that extraction of oil and gas via hydraulic fracturing will increase in five shale basins (e.g. Burgos, Sabinas, Tampico, Tuxpan, and Veracruz). Because hydraulic fracturing is a waterintensive activity, it is relevant to assess the potential water availability for this activity in Mexico. This research aims to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Compared with those carbonate hydrogenation, the proposed CaDRM strategy can be a more efficient way to change CO2 emissions into syngas production due to the fully atomic utilization efficiency of CH4 [29][30][31] . More significantly, in comparing with H2 source, CH4 possesses more advantages such as the abundancy in nature (nature gas), mature industrial applications, and most importantly being cost-effective 32,33 . Inspired by our previous study of integrated CO2 capture and conversion which explicitly identified the synergistic promotion of the carbonate reduction by CH4 for the regeneration 34 , we highly anticipate the CaDRM strategy can bring a disruptive technological revolution for achieving net-zero in the CO2 emission-intensive cement industry.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with those carbonate hydrogenation, the proposed CaDRM strategy can be a more efficient way to change CO2 emissions into syngas production due to the fully atomic utilization efficiency of CH4 [29][30][31] . More significantly, in comparing with H2 source, CH4 possesses more advantages such as the abundancy in nature (nature gas), mature industrial applications, and most importantly being cost-effective 32,33 . Inspired by our previous study of integrated CO2 capture and conversion which explicitly identified the synergistic promotion of the carbonate reduction by CH4 for the regeneration 34 , we highly anticipate the CaDRM strategy can bring a disruptive technological revolution for achieving net-zero in the CO2 emission-intensive cement industry.…”
Section: Introductionmentioning
confidence: 99%
“…For example, most previous studies that analyze the costs associated with unconventional fuel production do not address the costs (real or hidden) of accounting for the water availability required to perform fracking operations (e.g., [10], [11], [12]). Although some studies have related water-stressed regions with fracking activities [6], [13], [14], [15], only a few studies [16], [17], [18], attempted to quantify the potential impact of water used for fracking on the local and regional water resources. A recent national-scale assessment on water use for hydraulic fracturing in the US [20] calls for further studies that examine regional-scale energy and water sustainability challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have quantified water stress resulting from water withdrawals for hydraulic fracturing in some shale deposits in the United States, Argentina, China, and Mexico (e.g., Freyman, ; Galdeano et al, ; Guo et al, ; Mauter et al, ; Scanlon et al, ). In response to the need for a global‐scale analysis of the hydrologic impacts of shale extraction, the World Resources Institute estimated that 39% of global shale deposits lie within surface water‐stressed regions (Reig et al, ).…”
Section: Introductionmentioning
confidence: 99%